2021
DOI: 10.1097/inf.0000000000003277
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a 20-valent Pneumococcal Conjugate Vaccine in Healthy Infants in the United States

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…The response rates after a four-dose series for common serotype 6B and additional serotype 3 were lower than for other serotypes, which was consistent with our findings ( Ruiz-Aragón et al, 2013 ). It was also reported that in the immunogenicity of newly developed PCV20, the GMCs of 6B and 3 were lower than those in PCV13 ( Senders et al, 2021 ). However, we cannot completely understand the lower immunogenicity of serotypes 6B and 3.…”
Section: Discussionmentioning
confidence: 89%
“…The response rates after a four-dose series for common serotype 6B and additional serotype 3 were lower than for other serotypes, which was consistent with our findings ( Ruiz-Aragón et al, 2013 ). It was also reported that in the immunogenicity of newly developed PCV20, the GMCs of 6B and 3 were lower than those in PCV13 ( Senders et al, 2021 ). However, we cannot completely understand the lower immunogenicity of serotypes 6B and 3.…”
Section: Discussionmentioning
confidence: 89%
“…10,11,18-89 18 studies (20 publication records) were excluded from the analysis: 6 studies did not provide individual patient or aggregate data, [70][71][72][73] and 12 studies (14 publication records) were head-to-head studies with the vaccines of interest, but it was not possible to form a loop within the network meta-analysis to provide indirect evidence (See Supplementary Figure 1 and Supplementary Table 2). [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Of these 12 studies, 8 reported results from different PCVs including a new Cuban PCV7, PCV10-SII, PCV11, PCV12, a Chinese PCV13, PCV14, PCV15, PCV20, PCV24 and PCV SP0202-VI. The remaining 27 studies (53 publication records) from 2009 to 2022 were included in the network meta-analyses.…”
Section: Search Resultsmentioning
confidence: 99%
“…Generally, other disease endpoints including non-bacteraemic pneumonia may also be important for vaccine choice e.g., PCV13 is shown to be more efficacious in preventing VT non-bacteraemic pneumonia than PPV23 (46% vs 21%) [2], and if included in this analysis, it may likely heighten PCV13 impact to similar levels or higher than PPV23 in England, albeit with higher vaccine cost. With the likely upcoming use of PCV15 and PCV20 in infants in the near future [39], the vaccine preventable fraction of adult disease is likely to diminish correspondingly because of the indirect effects of such infant programme, and thus reducing the benefit of adult programmes that target the same serotypes as those targeted in infants. On the other hand, PCV21 targets most serotypes not targeted by PPV23 or PCV20 [40], which could likely improve tackling the remaining burden of pneumococcal disease in older adults, in the long absence of vaccines that target surface proteins common to all serotypes [41].…”
Section: Discussionmentioning
confidence: 99%